Analysis and Knowledge of Blood Groups and Attitudes Toward Blood Donation in Jordan - Alkhataybeh, Ahmad; Alkhataybeh, Banan (Jordan Medical Journal, 2022)
Background: This study aimed to determine the distribution of blood groups among Jordanian university students, investigate the Knowledge and attitudes toward blood donation among the study population. Also, it aimed at assessing any correlation between blood groups and achievement, geographical distribution, and gender. As well as, it aimed to investigate the personal Knowledge of blood group, the blood donations throughout life, matching of blood group compared to those registered in the governmental departments, ability to form a database of people who can donate blood. Methods: To attain the study's objective, a random sample of 830 Jordanian university students from different regions were selected. The researcher adopted an analytical and descriptive study. Results: The study revealed that the most prominent blood group among Jordanian university students is A group according to the ABO system and group O+ according to ABO and RH system. Also, it revealed that 93.6% had not donated blood. Conclusions: Blood group A was found to be the highest among the study population. 81.2% of the students were found to be RH+. Recording blood groups correctly and encouraging blood donation in the Jordanian community is critical for life-saving.